Contradictions within the SDGs: are sin taxes for health improvement at odds with employment and economic growth in Zambia - Peter Hangoma; Gavin Surgey (BMC, 2019)
Abstract Background A recurring discussion in the literature relates to the possible contradictions among the Sustainable Development Goals (SDGs). The focus has been on economic goals, such as economic growth and goals related to climate change. We explore the possible contradictions that may arise between economic goals and health goals, specifically, the goal on Non-Communicable Diseases (NCDs) - SDG3.4. As a way to achieve SDG3.4, countries have been urged to introduce sin taxes, such as those on sugar. Yet others have argued that such taxes may affect employment (SDG 8.5), economic growth (SDG 8.1), and increase poverty (SDG1). However, there is limited or no reliable evidence, using actual experience, on the effect of sugar tax on health and economic outcomes. This makes it hard to assess the possible contradictions in SDGs that sugar taxes may generate. Main body Using a conceptual framework on SDGs that views relationships among SDGs as either contradictory, reinforcing, or neutral, we carefully consider whether there are contradictions between SDG 3.4 on one hand and SDG 1, SDG 8.1, and SDG 8.5 on the other hand. We illustrate this using Zambia which recently introduced an equivalent 3% tax on non-alcoholic beverages, implicitly targeted at sugar-sweetened beverages (SSBs), given the stated goal of reducing NCDs. Concerns are that such a tax would be detrimental to the Zambia sugar value chain which contributes about 6% to GDP, in which case the achievement of SDG 3.4 (health) would be at odds with, or contradict, SDG 1, SDG 8.1, and SDG 8.5 (poverty eradication, economic growth, and creation of employment). We discuss that the existence of contradictions depend on a number of contextual factors, which allows us to make two conclusions about sugar taxation in Zambia. First, the current tax rate of 3% is likely neutral (no contradictions or reinforcing relationships) because it is too low to have any health or employment effects. However, the revenue raised can be reinvested to improve livelihoods. Secondly, the tax rate should be increased but care has to be exercised to ensure that the rate is not too high to generate contradictions. There will be need to carefully assess important parameters such as elasticities and explore alternative economic livelihoods. Conclusion Without paying due consideration to important contextual factors, Zambia and many LMIC risk experiencing contradictions among SDGs.